The Impact of the National Policy on Education (NPE) on Multilingual Proficiency in Nigeria - Udoye Ifeoma (My University, 2019)
About 450 languages are spoken in Nigeria with Hausa, Igbo and Yoruba as the major languages. In order to assign functional roles to the multiplicity of languages, the Federal Government promulgated the National Policy on Education (henceforth NPE) in 1977 stipulated that every Nigerian child must be proficient in his mother tongue and in a major Nigerian language. At the secondary level, it is expected that every child should be bilingual in two Nigerian languages. Thirty six years later, the impact of the policy on the language education of Nigerian pupils was assessed. Data were collected using questionnaire and interview methods. Findings revealed that the primary aim of the NPE has not been achieved. Based on the findings, the recommendation made include the organization of intensive workshop sessions for language teachers to expose them to the modern techniques for attaining bilingualism through effective training.
Keywords: National Policy; Education; Language; Nigeria